(untitled) (Cardiovascular Journal, 2014)
Background- Hypertrophic cardiomyopathy (HCM) is a genetically transmitted disease with diverse natural history for which the potential to produce adverse consequences has been emphasized. However, the possibility of this disease remaining clinically dormant for many years has not been as widely appreciated. Certainly, the clinical recognition of previously undiagnosed patients with HCM may be advantageous by permitting risk stratification for sudden cardiac death or for timely pharmacologic therapy when symptoms intervene. The purpose of this study was to assess the disease pattern and the extent to which hypertrophic cardiomyopathy (HCM) exists undetected in a suspected group of population never diagnosed to have any cardiovascular disease, referred from the primary care facilities to one of the largest tertiary level hospital of Bangladesh. Methods-We prospectively conducted an echocardiographic survey in 3648 cases between 19-03-2009 to 03-08-2010 (18 months) in the cardiac centre of Combined Military Hospital, Dhaka, Bangladesh. Results- A total of 3648 cases referred by primary care physicians underwent echocardiogram either to confirm a new diagnosis or to exclude obvious cardiovascular abnormalities. Hypertrophic cardiomyopathy was identified in 148 patients (4.06%) who was not known have any cardiac disease before. At diagnosis, age ranged from 20 to 83 years (mean 52.19) with male gender preponderance (85.81%). Ninety eight patients (67%) had no functional limitation and the remaining fifty patients reported with symptoms mostly giving multiple responses like chest pain (39.2%), palpitation (18.9%), dyspnoea (22.3%), unusual fatigability (16.9%) and syncope (6.8%). Twelve patients had strong suspicion of familial predisposition depending on the symptomatology of the familial tree but were confirmed only in 03 cases by echocardiography. Basal left ventricular outflow obstruction (gradients 20 to 76 mm Hg) was evident in 14 patients (9.45%). Relatively variable phenotypic expression of the disease was substantiated by diffuse thickening of left ventricular wall occurring more commonly than localized distributed hypertrophy (56.08% vs. 43.94%, respectively). Electrocardiogram was abnormal in almost 95% of cases and typical pattern of left ventricular hypertrophy was observed in 25.68% cases. Conclusion -This prospectively assembled data show that HCM cases may remain asymptomatic, clinically dormant and undetectable for many years (often to advance ages) in our community. The actual prevalence of the disease in our community needs to be ascertained which might exceed the prevalence mentioned in the text books. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20798 Cardiovasc. j. 2014; 7(1): 31-37